Simulation of Compression in the Cavity of the Microwave Pulses with Output Energy of the Transformation of the Oscillations; Известия вузов. Физика; Т. 55, № 10-3 - Igumnov V. S. Vladislav Sergeevich; Avgustinovich V. A. Vladimir Andreevich; Artemenko S. N. Sergey Nikolaevich; Novikov S. A. Sergey Avtonomovich; Yushkov Y. G. Yuri Georgievich (2012, 2012)
Title screen